Judy Moody saves the world! - McDonald, Megan; Reynolds, Peter, 1961- (Cambridge : Candlewick Press, 2004)
When Judy Moody gets serious about protecting the environment, her little brother Stink thinks she is overdoing it, but she manages to inspire her third grade class to undertake an award-winning, environment-saving project.
500
Accelerated Reader AR
Keywords: Environmental protection -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Schools -- Juvenile fiction; Contests -- Juvenile fiction; Virginia -- Juvenile fiction; Humorous stories